Phono-strategic language preference for Andalusian Spanish (L2) over German (L1) in lisping bilinguals: an exploratory case study - Kozanda, Dominik (Journal of Monolingual and Bilingual Speech, 2022)
This paper investigates the preference for Andalusian Spanish (second language, L2) over German (first language, L1) in bilinguals who have a lisp and do not encounter a feeling of belonging to their L1 society due to reactions such a divergent pronunciation provokes. This issue is novel due to its interdisciplinary nature within this unique language combination, and it draws particularly on the fields of speech (pathology), language preference, communication, bilingualism, phonetics, psycholinguistics and sociolinguistics. To test the hypothesis ‘some bilinguals who have a lisp prefer to use Andalusian Spanish (their L2) over German (their L1) to avoid the noticeability of their speech divergence’, within the boundaries of the present exploratory case study, interviews with participants were recorded. It was found that participants sacrifice the usage of their L1 in favour of their L2 in an attempt to vanish their phonetic divergence. Such a finding is important because in Andalusian Spanish the pronunciation of the /s/ is significantly reduced during the conversation flow on account of many of the language’s specific phonetic conventions.